QUALITY OF PUBLIC SERVICES AT THE DEPARTMENT OF INVESTMENT AND INTEGRATED LICENSING SERVICES ONE DOOR OF THE GOVERNMENT OF NORTH SUMATRA PROVINCE - Muti Sinaga; Budi Hartono; Rudi Salam Sinaga (Universitas Negeri Medan, 2021)
Problems regarding the quality of public services have always been a concern in the study of public policy. The office of investment and licensing services is one of the agencies that is able to increase regional income. The purpose of this study was to determine the quality of public services at the One Stop Integrated Investment and Licensing Service of the North Sumatra Provincial Government. The method used is qualitative with the type of case study. Data obtained through interviews, literature study and documentation. Data analysis used descriptive analysis with data validity techniques using triangulation techniques. The results of the study found that human resources and the availability of infrastructure were the triggers for the decline in the quality of public services at the location of this study.